KONSEP EKONOMI KERAKYATAN BERBASIS HUKUM TRANSENDENTAL - Ratna Riyanti; Maheswara Edi Harnantio (Jurnal Kelola: Jurnal Ilmu Sosial, 2022)
An economic system based on the paradigm of Pancasila values, placing the position of the people as the Caliph of Allah SWT on earth, oriented to the common good is what is meant by People's Economy (economic democracy). There is a fundamental difference between the economic system in a country that adheres to a liberal-capitalist democracy and a socialist democracy, the Pancasila populist economy, and an economy that is developed within the framework of spiritual values ​​such as the value of divinity (Tawhid). The emergence of political investors whose interests are accommodated from the transactional system, including the hegemony of capitalism which has an effect on globalization, causing the market in the financial center of national boundaries, is the application of a democratic system that comes out of the values ​​and paradigms of Pancasila. This is an ideological problem, so that the transcendental dimension in the populist economy needs to be re-grown to fight the threat of globalization and new forms of capitalism, by restoring the transcendent values ​​of Pancasila into the building of economic, legal and political systems in Indonesia.